2016
DOI: 10.1039/c6nr04310k
|View full text |Cite
|
Sign up to set email alerts
|

3D nanostructured inkjet printed graphene via UV-pulsed laser irradiation enables paper-based electronics and electrochemical devices

Abstract: Emerging research on printed and flexible graphene-based electronics is beginning to show tremendous promise for a wide variety of fields including wearable sensors and thin film transistors. However, post-print annealing/reduction processes that are necessary to increase the electrical conductivity of the printed graphene degrade sensitive substrates (e.g., paper) and are whole substrate processes that are unable to selectively anneal/reduce only the printed graphene-leaving sensitive device components expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(147 citation statements)
references
References 55 publications
3
143
1
Order By: Relevance
“…40 Additionally, this laser annealing process, performed in ambient air, increases the number of superficial defects while adding oxygenated species (COOH, −CO, and −OH) to the said defects as previously reported. 42 The increase of graphene superficial defects has been shown to significantly increase the nucleation density of PtNPs during electrodeposition.…”
Section: 39mentioning
confidence: 83%
“…40 Additionally, this laser annealing process, performed in ambient air, increases the number of superficial defects while adding oxygenated species (COOH, −CO, and −OH) to the said defects as previously reported. 42 The increase of graphene superficial defects has been shown to significantly increase the nucleation density of PtNPs during electrodeposition.…”
Section: 39mentioning
confidence: 83%
“…Inkjet printing of the extract closely followed our similar procedures for printing graphene inks . For preparing inkjet‐printed thin film biodetectors, aliquots (3 mL) of extract were filtered through a 0.45 µm.…”
Section: Methodsmentioning
confidence: 99%
“…The printed line morphology resulting from the drop spacing and the working temperature control edge effects (known as the coffee ring effect). Our previous work shows that average film thickness is between 3 and 5 µm, classifying this structure as a thin film . A circular array was designed using computer‐aided design (CAD software) and inkjet printed.…”
Section: Methodsmentioning
confidence: 99%
“…This research team engineered an SPR substrate based on a GO-coated Au surface for the screening of a cardiac biomarker (galectin-3), reaching a clinically relevant concentration range. [115] Moreover, GO leads to generation of flexible membrane-like SERS substrates than can be utilized as pre-concentration platforms for highly sensitive analysis of large volumes. They also concluded that the SPR sensitivity was observed to be proportional to the thickness of the explored GO coating.…”
Section: Go In Label-free Optical Biosensingmentioning
confidence: 99%